1999
DOI: 10.1093/jnci/91.23.2009
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Tobacco Smoke, Genetic Susceptibility, and Risk of Lung Cancer in Never-Smoking Women

Abstract: A common genetic polymorphism divides the population of never smokers into two groups of approximately equal size, one (homozygous carriers of the GSTM1 null allele) that has a statistically significant greater risk of lung cancer from ETS than the other (heterozygous or homozygous carriers of the wild-type GSTM1 allele).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
92
1
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(101 citation statements)
references
References 39 publications
6
92
1
2
Order By: Relevance
“…In addition, Hecht et al 13 have measured urinary metabolites of the tobacco-specific carcinogen NNK and have found that never smokers exposed to ETS have 2-5% levels of active smokers, a higher level than expected on the basis of the exposure level. Bennett et al 14 have found that, when compared to never smokers who had no ETS exposure, never smokers with exposure to ETS who developed lung cancer were more likely to be deficient in GSTM1 activity (i.e., were GSTM1 null) (odds ratio ϭ 2.6; 95% confidence interval 1.1-6.1). Therefore, it is not unreasonable to hypothesize that the observed relative risks in lifetime nonsmokers exposed to ETS are due to a subpopulation of more susceptible individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Hecht et al 13 have measured urinary metabolites of the tobacco-specific carcinogen NNK and have found that never smokers exposed to ETS have 2-5% levels of active smokers, a higher level than expected on the basis of the exposure level. Bennett et al 14 have found that, when compared to never smokers who had no ETS exposure, never smokers with exposure to ETS who developed lung cancer were more likely to be deficient in GSTM1 activity (i.e., were GSTM1 null) (odds ratio ϭ 2.6; 95% confidence interval 1.1-6.1). Therefore, it is not unreasonable to hypothesize that the observed relative risks in lifetime nonsmokers exposed to ETS are due to a subpopulation of more susceptible individuals.…”
Section: Discussionmentioning
confidence: 99%
“…However, findings reported by Georgiadis et al (2004) indicate that nonsmoking students exposed to urban air pollution and ETS with GSTM1 deletion had higher levels of DNA adducts in their lymphocytes compared with GSTM1 ''wild-type'' participants. Never-smoking women with GSTM1 null had statistically significant greater risk of developing lung cancer from exposure to ETS (Bennett et al, 1999). Lung cancer risk in GSTM1-null individuals exposed to indoor coal combustion emissions was elevated compared with individuals with an active copy of GSTM1.…”
Section: Introductionmentioning
confidence: 90%
“…Other mechanisms that have been reported to play a role in determining the carcinogenic potential are alterations in the detoxification of carcinogenic compounds, which are mediated by the conjugation of the compounds or their metabolites to glutathione by glutathione S-transferase (GST). GSTs are class II detoxification enzymes that are encoded by four classes of polymorphic genes [Bennett et al, 2000].…”
Section: Introductionmentioning
confidence: 99%